THE PRACTICE OF PHYSICAL ACTIVITY AND ITS RELATIONSHIP WITH THE MOTOR COORDINATION LEVEL IN CHILDREN WITH DOWN SYNDROME (Fiep Bulletin - online, 2016)
The motor development in childhood, characterized by the acquisition of motor skills, which nurture a body area. These skills are required in the daily life of the child, thus the present study aimed to evaluate the performance level of large motor skills in children with Down Syndrome between 8 and 12 years old and their relationship with physical activity. The sample consisted of 15 students with ± 10.2 years old, including 8 boys and 7 girls from Mãe D'água's project of the city of Joinville-SC. The children motor performance was measured by KTK (GORLA, 2007) test battery and questionnaire of weekly physical activities. Statistical analysis was performed using Student's T-Test. In general the results of the study revealed that 73.3% of the sample showed a poor performance. As for the motor performance components coordinated, it was found that girls showed more difficulties in lateral jumps and monopedal than boys, who had lower levels of balance. Physical activity did not show significant results of a better motor performance in individuals of this sample and advancing age has generated a decrease in motor coordination levels of the sample.
Keywords: Down syndrome; physical activity; motor performance.